2011
DOI: 10.1111/j.1369-7625.2011.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of chronic pain patients’ perceptions of home telerehabilitation services

Abstract: Objectives To explore patientsÕ perceptions regarding prospective telerehabilitation services and the factors that facilitate or impede patientsÕ intentions to use these services.Design Using semi-structured interviews, patients reflected on the pros and cons of various scenarios of prospective telerehabilitation services. PatientsÕ arguments were first arranged according to the Unified Theory of Acceptance and Use of Technology (UTAUT). Next, using inductive analysis, the data for each UTAUT component were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 39 publications
11
110
0
2
Order By: Relevance
“…Typically, sociodemographic characteristics such as younger age, higher educational level, Internet access, and technical experience have been associated with acceptance of eHealth interventions in several studies [2,27,49,50]. Further potential barriers to acceptance include Internet anxiety [40,51], low Internet orientation in health problems [27], insufficient knowledge of eHealth interventions [27,52], rural residence [53], or reservations regarding data security or impersonal interaction [54,55]. However, barriers or facilitators to eHealth adoption in inpatient routine care have not been studied sufficiently yet.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, sociodemographic characteristics such as younger age, higher educational level, Internet access, and technical experience have been associated with acceptance of eHealth interventions in several studies [2,27,49,50]. Further potential barriers to acceptance include Internet anxiety [40,51], low Internet orientation in health problems [27], insufficient knowledge of eHealth interventions [27,52], rural residence [53], or reservations regarding data security or impersonal interaction [54,55]. However, barriers or facilitators to eHealth adoption in inpatient routine care have not been studied sufficiently yet.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies examined chronic pain sufferers’ perspective of in-home telerehabilitation. The first used semi-structured interviews with participants who were informed about possible telerehabilitation services [24]. The second used a questionnaire based on the Technology Acceptance Model (TAM) with participants randomly allocated either to an experimental group who got information about and could try out a web-based program which provided selected instructional videos or a control group who only got information about the web-based program [25].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the fields of chronic disease and rheumatology also found that participants considerably value face-to-face supervision of a healthcare professional [30,31]. Furthermore, it is known that multiple communications with clinicians result in less dropout and better adherence to interventions [32].…”
Section: Discussion Principal Resultsmentioning
confidence: 99%